Department of Educational and Psychological Sciences/Curricula and Teaching Methods Postgraduate - Dr. Abbas Lafta Hassan; Suhad Hassan Shuwaikh (Migration Letters, 2023)
The current research aims to firstly: Develop an educational program based on the Hameros model to enhance the achievement of students in the field of social psychology at the Colleges of Education. Secondly: Investigate the effectiveness of the educational program in enhancing the achievement of second-year students at the College of Humanities Education - Wasit University. Derived from this objective is the following hypothesis: There are no statistically significant differences at the (0.05) level between the mean scores of the experimental group, which studied social psychology according to the educational program, and the mean scores of the control group, which studied the same subject using the conventional vocabulary (as prescribed by the committee of deans) using the traditional post-achievement test. To achieve the research objective, the researcher utilized a partial control experimental design (pre-test and post-test) for equivalence purposes, and the sample size consisted of (106) male and female students from the College of Education at Wasit University, Department of Educational and Psychological Sciences. The researcher selected the research sample purposively, with (52) students in the experimental group who studied the educational material according to the established educational program based on the Hameros model, and (54) students in the control group who studied the educational material using the conventional method. The researcher controlled for equivalence in the following variables: chronological age (calculated in months), intelligence, and prior knowledge. To achieve the research objective and test its hypothesis, the researcher developed an educational program based on the Hameros model. This program included educational objectives, diverse teaching strategies, accompanying activities, instructional materials, and various assessment methods. To obtain the results of the current research, the researcher prepared a research instrument, which was represented by the achievement test consisting of (40) test items, including (29) objective items. The selection of the items was done with four alternatives to measure levels of recall, comprehension, and application. Additionally, there were (11) essay-type items to measure levels of analysis, synthesis, and evaluation. The test was reviewed by experts and specialists in the field and served as a reliable measurement tool. The researcher personally administered the test to both research groups to avoid any potential errors or differences in the abilities of the instructor. Prior to the commencement of the experiment, the two groups were equated, and the researcher used two research methods. First, a descriptive method was employed to construct the educational program based on the predetermined syllabus provided by the committee of deans for teaching social psychology. The second method was experimental, aiming to determine the effectiveness of the educational program in enhancing the achievement of social psychology among the research sample.